Nonlinear dynamic response and vibration of FG CNTRC shear deformable circular cylindrical shell with temperature-dependent material properties and surrounded on elastic foundations. (October 2019) - Van Thanh, Nguyen; Dinh Quang, Vu; Dinh Khoa, Nguyen; Seung-Eock, Kim; Dinh Duc, Nguyen
Based on Reddy's first-order shear deformation theory, the nonlinear dynamic response and vibration of imperfect functionally graded carbon nanotube-reinforced composite (FG CNTRC) circular cylindrical shells subjected to an external dynamic load uniformly distributed on the surface of the shell and axial compression in thermal environment are presented. The circular cylindrical shells are surrounded on elastic foundations and reinforced by single-walled carbon nanotubes which vary according to the linear functions of the shell thickness. The shell's effective material properties are assumed to depend on temperature and estimated through the rule of mixture. By applying the stress function, Galerkin method and fourth-order Runge–Kutta method, nonlinear dynamic response and natural frequencies for imperfect FG CNTRC circular cylindrical shells are determined. In numerical results, the influences of geometrical parameters, elastic foundations, initial imperfection, temperature increment, dynamic loads and nanotube volume fraction on the nonlinear vibration of FG CNTRC circular cylindrical shells are investigated. The obtained results are validated by comparing with those of other authors.